Republic of Estonia : 2021 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
Macroeconomic performance and buffers were strong when the COVID-19 pandemic hit. Economic and social restrictions instituted in March 2020 helped slow new infections and mitigate negative health outcomes but triggered a deep decline in activity in Q2:2020. The slump was followed by a strong rebound in Q3 as the restrictions were eased. With the resurgence of the virus, pressures on the health system peaked in late-March 2021 and eased after a new round of restrictions. Going forward, the outlook is for a near-term economic recovery subject to large two-way risks. The strength and durability of the recovery hinges on the evolution of the health situation and the extent of economic scarring from the pandemic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Estonia, Republic of